1975
DOI: 10.1002/jsfa.2740261210
|View full text |Cite
|
Sign up to set email alerts
|

A survey of volatile components of some allium species in terms of s‐alk(en)yl‐l‐cysteine sulphoxides present as flavour precursors

Abstract: The volatile flavour components of 27 Allium species and cultivars, mostly edible but including some decorative species for comparison, have been investigated by a series of gas and thin-layer chromatographic and U.V. spectrophotometric methods. By means of simulation experiments with synthetic precursors and intermediates, the data have been interpreted in terms of the amino acid precursors present in the intact tissues and the species classified as containing (a) S-1-propenyl-, (b) S-2-propenyl-and (c) S-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
4

Year Published

1977
1977
2005
2005

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(58 citation statements)
references
References 19 publications
2
50
1
4
Order By: Relevance
“…The level of PCSO, the main sulfur precursor in leek (Freeman and Whenham, 1975), was measured on a 10-cm segment of the stalk using the Waters Pico-Tag technique (Bidlingmeyer et al, 1984). The sample was weighed and ground in methanol for 40 sec at atmospheric pressure.…”
Section: Methodsmentioning
confidence: 99%
“…The level of PCSO, the main sulfur precursor in leek (Freeman and Whenham, 1975), was measured on a 10-cm segment of the stalk using the Waters Pico-Tag technique (Bidlingmeyer et al, 1984). The sample was weighed and ground in methanol for 40 sec at atmospheric pressure.…”
Section: Methodsmentioning
confidence: 99%
“…treated Chromosorb W. 80-100 mesh. This procedure is similar to that used by Freeman and Whenham (1975) and the procedure and results are described in detail by ElGadi (1976). Major compounds were provisionally identified by gas chromatography-mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…Volatile sulphides produced after tissue damage have been investigated, since it has been shown (Saghir, Mann and Yamaguchi, 1965;Saghir, Mann, Ownbey and Berg, 1966;Bernhard, 1970;Freeman and Whenham, 1975) that there is substantial variation between taxa of Allium in the composition of the sulphides produced and that these are readily separable by gas-liquid ehromatography.…”
Section: In ] 84mentioning
confidence: 99%
“…S-Alk( en)yl-L-cysteine sulfoxides serve as precursors of flavor in the genus. An investigation of 27 Allium species found that they could be placed into three groups based on the predominance of certain amino acid precursors (Freeman and Whenham 1975). The predominant precursors were S-1-propyl (onion), S-2-propenyl (garlic), and S-methyl (A. aflaturense B. Fedtschenko) cysteine sulfoxides.…”
Section: Flavor Formation From Cysteine Sulfoxide Derivativesmentioning
confidence: 99%